Antibacterial effects of cinnamon (Cinnamomum zeylanicum) bark essential oil on Porphyromonas gingivalis. (March 2018) - Wang, Yue; Zhang, Yi; Shi, Yan-qin; Pan, Xian-hua; Lu, Yan-hua; Cao, Ping
Abstract: The objective of this study was to investigate the antibacterial effects of cinnamon ( Cinnamomum zeylanicum ) bark essential oil (CBEO) and its principal constituent cinnamaldehyde against Porphyromonas gingivalis and to elucidate the antibacterial mechanism. GC-MS analysis showed that cinnamaldehyde was the major constituent in CBEO (57.97%). The minimum inhibition concentrations (MICs) of CBEO and cinnamaldehyde were 6.25 μg/mL and 2.5 μM for P. gingivalis, respectively. Nucleic acid and protein leakage was observed with increasing concentrations of CBEO and cinnamaldehyde. Additionally, propidium iodide uptake assays revealed CBEO and cinnamaldehyde at 1 × MIC impaired P. gingivalis membrane integrity by enhancing cell permeability. Morphological changes in P. gingivalis cells were observed by scanning electron microscopy, which indicated cell membrane destruction. To further determine the anti -biofilm effect, relative biofilm formation and established biofilms were examined, which demonstrated that both CBEO and cinnamaldehyde at sub-MIC levels inhibited P. gingivalis biofilm formation by 74.5% and 67.3% separately, but only CBEO slightly decreased established biofilms by 33.5% at 4 × MIC. These results suggest the potential of CBEO as a natural antimicrobial agent against periodontal disease. Furthermore, cinnamaldehyde was confirmed to be the antibacterial substance of CBEO with inhibitory action against P. gingivalis . Highlights: CBEO exhibited a strong antibacterial activity against planktonic P. gingivalis. CBEO and the principal constituent cinnamaldehyde damaged the cell membrane of P. gingivalis. CBEO and cinnamaldehyde inhibited biofilm formation of P. gingivalis. Cinnamaldehyde was confirmed to be the antibacterial substance of CBEO. CBEO and cinnamaldehyde are antimicrobial agents against periodontal disease.